Perancangan Aplikasi Sistem Informasi Sebagai Media Promosi Menggunakan Bahasa Pemrograman Php Dan Database Mysql Pada Amanah Auto Rental - Jaya, Lindo; Akbar, Fauzan; Putra, Arief (Jurnal Sains Informatika Terapan, 2022)
Current technological advances can help to processing the data, which the need of a computer is necessary, knowing that the required data formats and reports need to be a good and proper reports. Therefore a good system is needed for the benefit of the car rental business, which will provide convenience, accuracy, and speed in providing information to customers and all those in need. The purpose of this study is to design, testing and give an implementation of web-based information systems to Amanah auto rental officer.the programming language used is PHP using MySQL database. This web-based information system car rental can give convenience to the prospective customers to see cars leased and rental cars are available at. Moreover, it can give convenience to the Amanah auto rental officer to provide information - information about rent car.